Toward Interfaith Equality in Islamic Inheritance Law: Discourse and Renewal of Judicial Practice in Indonesia - Riyanta; Najib, Agus Moh.; Bahiej, Ahmad; Falah, Mohammad Bachrul (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
The Supreme Court of Indonesia has granted portions of inheritance to non-Muslim relatives through the legal mechanism of wasiat wājibah (obligatory will), based on considerations of propriety and limited to no more than one-third of the estate. This article examines how the Supreme Court establishes the legal basis, rationale, and relevance of applying wasiat wājibah to non-Muslim relatives, and how this practice contributes to the reform of Islamic inheritance law in Indonesia. The study employs a normative legal research method with a case based approach. The findings reveal that the Supreme Court’s decisions to award wasiat wājibah to non-Muslim relatives represent a form of judicial innovation aimed at achieving maslahah (public benefit) among heirs. However, the application of wasiat wājibah remains case-specific, determined by the perceived benefit within the personal relationship between a Muslim testator and their non-Muslim relatives. These rulings hold significant relevance for the reform of Islamic inheritance law in Indonesia. First, conceptually, Islamic inheritance law falls under the domain of mu‘āmalah (civil transactions), which allows for reinterpretation and contextualization based on local realities. Second, the implementation of wasiat wājibah reflects a constructive response to the evolving social and legal dynamics of Indonesia’s pluralistic society.